2020
DOI: 10.1186/s12891-020-03425-9
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of kinematics in knees after single versus multiple radius femoral prostheses total knee arthroplasty: a retrospective study

Abstract: Background Design modifications in prostheses may cause alterations in gait kinematics, thus influencing functional restoration of knees after total knee arthroplasty (TKA). The aim of the study was to investigate the differences in gait kinematics and clinical outcomes after single radius (SR) versus multiple radius (MR) TKA. Method The present retrospective study included 38 unilateral TKA involving 20 knees using MR design implant and 18 knees using SR design implant. Thirty-six healthy volunteers were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The DOFs rotating around the coordinate axes includes: internal/external rotation angle, internal/external flip angle, flexion/extension angle. The DOFs translated along the coordinate axes includes: anterior/posterior displacement, superior/inferior displacement, and internal/external displacement [ 32 , 33 ]. During practice, the participant is asked to undergo approximately 2–3 min of acclimatization.…”
Section: Discussionmentioning
confidence: 99%
“…The DOFs rotating around the coordinate axes includes: internal/external rotation angle, internal/external flip angle, flexion/extension angle. The DOFs translated along the coordinate axes includes: anterior/posterior displacement, superior/inferior displacement, and internal/external displacement [ 32 , 33 ]. During practice, the participant is asked to undergo approximately 2–3 min of acclimatization.…”
Section: Discussionmentioning
confidence: 99%
“…In a fluoroscopic assessment of the knee during exercise, Pandit et al reported that in the sagittal plane, a more “natural kinematic” design of a posterior‐stabilized implant allows for greater movement and is more physiological [30], and is associated with improved physiological restitution of the gait in flexion–extension [22, 23, 25].…”
Section: Discussionmentioning
confidence: 99%
“…The 6DOF values obtained for the right knee joint with and without the OUB were analyzed for all subjects, with proximal-distal translation, abduction-adduction rotation, and internal-external rotation of the knee joint serving as primary reference indexes, and with internal-external translation, anterior-posterior translation, flexion-extension angle serving as secondary indexes. Among the primary indices, proximal-distal translation may reflect knee joint gap [ 21 ], abduction-adduction rotation can reflect variation of the inner and outer loads in the TF joint [ 22 ], and internal-external rotation can reflect comfort to some degree; the secondary indices can reflect the contribution of a brace to knee joint stability.…”
Section: Methodsmentioning
confidence: 99%